PENGARUH APLIKASI QUIZIZZ SEBAGAI MEDIA EVALUASI FORMATIF TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA DI KELAS V UPT SD NEGERI 14 BINAMU KABUPATEN JENEPONTO - Bahri, Aliem; Putri Rahmadani; Ratnawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Effect of Using Quizizz Application as a Formative Evaluation Media on Students’ Learning Outcomes in Indonesian Language for Grade V at UPT SD Negeri 14 Binamu, Jeneponto Regency. Thesis. Elementary School Teacher Education Department, Faculty of Teacher Training and Education, Universitas Muhammadiyah Makassar. Supervised by Aliem Bahri as the first supervisor and Ratnawati as the second supervisor.This study was motivated by the low learning outcomes and motivation of students in participating in Indonesian language formative evaluation in Grade V at UPT SD Negeri 14 Binamu, as well as the limited use of interactive evaluation media. This condition indicates the need for innovation in formative assessment through the use of digital technology such as the Quizizz application, which is based on gamification and can increase student engagement in the learning process. This study aims to determine the effect of using Quizizz as a formative evaluation media on students’ Indonesian language learning outcomes in Grade V at UPT SD Negeri 14 Binamu, Jeneponto Regency.This research employed a quantitative approach with a Pre-Experimental One Group Pretest-Posttest Design and a Nonequivalent Control Group Design. The sample consisted of 40 students, divided into an experimental class (V-A) and a control class (V-B). Data were collected through learning outcome tests (pretest and posttest) and analyzed using normality tests, homogeneity tests, and hypothesis testing with a paired sample t-test.The results showed that the use of Quizizz improved students’ activity and engagement in the learning process. Students in the experimental class were more enthusiastic and active in answering questions compared to those in the control class, which used conventional methods. In addition, there was a significant increase in learning outcomes in the experimental class, where the average posttest score was higher than the pretest score. The hypothesis test results showed a significance value of 0.000 < 0.05, indicating that there is a significant effect of using Quizizz on students’ learning outcomes.Based on the findings, it can be concluded that the use of Quizizz as a formative evaluation media has a positive effect on the Indonesian language learning outcomes of Grade V students at UPT SD Negeri 14 Binamu, Jeneponto Regency. Learning outcomes improved through formative evaluation using the Quizizz application.